In-Silico Analysis of Avr-Pik and AvrPiz-t from Pyricularia oryzae (Cavara) - Najaa Batrisyia, Abdullah Zakaria (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Pyricularia oryzae (Cav.) is an ascomycete fungal pathogen that causes rice blast disease and has been a concern worldwide. Avr genes of P. oryzae have been reported in Sarawak, however, a further study on genetic population diversity and Avr-R interactions have not been focused. The focus of this study is to analyse the genetic variations and assess probabilities of different haplotypes of Avr-Pik and AvrPiz-t of Sarawak isolates to interact with the corresponding Pik and Piz-t alleles. The gene sequences of Sarawak isolates were compared with Avr genes 7’ of Sarawak isolate retrieved from NCBI. The result revealed that the Avr genes had genetic variations and had high genetic diversity when compared to gene sequences of China and Japan isolates. Subsequently, several motifs were detected in Avr proteins which mostly involved in signal transduction pathways. Based on molecular docking, all Avr proteins of Sarawak isolates were predicted to be recognized by the R alleles, however, differ in cluster scores, thus showing allelic interaction. This implies that, the Avr-R recognition in the field might not activate defence responses in rice. Therefore, further study on Rice-Pyricularia pathosystem may aid control of rice blast disease